Persepsi Pedagang Terhadap Relokasi Pasar Baru Kota Tanjungpinang - Arifin Arifin; Febry Chahyadi Anugrah; Rizky Octa Putri Charin (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
The new market, tanjungpinang, is helping the economy and helping people's needs, but at present the new market is very low. The collapse of the new market occurred on March 5, 2022 a.m., at 09.45 a.m. As a result of the incident, tanjungpinang mayor made a new market relocation policy to the jaya jungle and teuku umar road. The study agreed to explain what factors affected the relocation of new markets. This information and research is a new market trader of seven people, using the simple random sample technique. As a result of research on the traders' response to new market relocations, the cost of transportation to the merchants' own movement and the sale of merchants refused to sign a declaration letter. But many of the traders who agree to the move as the condition of their merchandise is no longer viable. The merchants hoped that the market relocation would be better and more comfortable in order for merchants and buyers to do good business, as well as for the merchants reconstructing of new markets to be tidy and that the merchants would be forced to obtain suitable trading places.